Identification of sequences regulating the transcription of a Dictyostelium gene selectively expressed in prespore cells. - Early, A E (1989)
There has been considerable debate about the relative contributions of transcriptional and post-transcriptional mechanisms to the regulation of prespore gene expression in Dictyostelium. We have determined the DNA sequence upstream of D19, the Dictyostelium gene encoding PsA, a prespore-specific, cell surface protein of unknown function. Our analysis of gene fusions, in which D19 upstream sequences are placed adjacent to a heterologous reporter gene, indicates that transcriptional signals alone are sufficient for the correct temporal and cell-type specific expression of this gene. We also show that the 5' and 3' boundaries of the minimal sequences necessary for correct developmental regulation lie within the region 338 to 122 nucleotides upstream of the start site of transcription but that flanking sequences seem to be necessary for optimal expression.